Influence of Calcination Temperature on Particle Size and Photocatalytic Activity of Nanosized NiO Powder - Pranwadee Kaewmuang (2018)
© 2018, Pleiades Publishing, Ltd. Abstract: Nanosized NiO particles were synthesized by a combined solvothermal-calcination process using Ni(NO3)2 · 6H2O as a starting reagent in the presence of ethylene glycol. The effect of varying the calcination temperature from 500 to 700°C on crystallinity and particle size of the synthesized NiO nanoparticles was investigated. The crystallinity and particle size of the NiO nanoparticles increased with increasing calcination temperatures. The particle size–photocatalytic activity relationship of the synthesized NiO nanoparticles was investigated. It was found that the NiO with smaller particle size and larger surface area shows strong UV–Vis absorption. The NiO nanoparticles calcined at 500°C degraded Congo red under the xenon light better than those calcined at higher temperatures.